Performance evaluation of low-cost IoT based chlorophyll meter - Heri Andrianto; Suhardi Suhardi; Ahmad Faizal (Institute of Advanced Engineering and Science, 2020)
Nutrient deficiencies in plants can be identified using a chlorophyll meter. However, current chlorophyll meters are still expensive and have many disadvantages. In this paper, a low-cost IoT-based chlorophyll meter has been developed. The performance of a low-cost IoT-based chlorophyll meter has been compared with the performance of a spectrophotometer (SP-3000nano) and a commercial chlorophyll meter (SPAD-502). A low-cost IoT-based chlorophyll meter has been functioning properly which is able to measure the chlorophyll content of plants in the field, get positions based on GPS satellites, store data in a memory module, and send data to the service system platform. The test results showed the coefficient of determination (R2) between SPAD-502 values and low-cost IoT-based chlorophyll meter values is 0.9705, this shows a significant correlation. An IoT-based chlorophyll meter can be used as a cheap alternative to the SPAD-502 chlorophyll meter.